2012
DOI: 10.1016/s0924-9338(12)74426-7
|View full text |Cite
|
Sign up to set email alerts
|

P-259 - Prevalence of adolescent depression in Europe

Abstract: Background: According to previous studies the prevalence of adolescent depression is 4-8% both in the USA and Europe. The aim of the current study was to investigate the prevalence of adolescent depression separately in several European countries. Method: Data were drawn from the Saving and Empowering Young Lives in Europe (SEYLE) study, which included 11 countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
1
16
1
1
Order By: Relevance
“…The prevalence of depressive symptoms among adolescents varies greatly between different countries and regions. A study based on 11 European countries (e.g., France, Germany, and Italy) found that the rate of depressive symptoms in adolescents ranged 7.1% to 19.4% [11]. In Asia, according to a school-based study in North India, the prevalence of depressive symptoms amongst adolescents has reached 40% [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of depressive symptoms among adolescents varies greatly between different countries and regions. A study based on 11 European countries (e.g., France, Germany, and Italy) found that the rate of depressive symptoms in adolescents ranged 7.1% to 19.4% [11]. In Asia, according to a school-based study in North India, the prevalence of depressive symptoms amongst adolescents has reached 40% [12].…”
Section: Introductionmentioning
confidence: 99%
“…Específicamente, se estima que la prevalencia de la depresión en adolescentes alcanzaría aproximadamente al 14% de la población, en tanto que los trastornos ansiosos estarían presentes en un 32% (Balazs et al, 2012;Merikangas et al, 2010). En Chile la prevalencia de estos trastornos superaría el 7% de la población, siendo de los más frecuentes en el tramo de 12 a 18 años de edad (De la Barra, Vicente, Saldivia, & Melipillán, 2012).…”
Section: Discussionunclassified
“…In 2014, an estimated 2.8 million adolescents in the United States experienced at least one major depressive episode, representing 11.4% of the underage U.S. population (Hedden, 2015). Representative data from European countries illustrate similar rates among adolescents (7.1%–19.4%) with regional differences (Balazs et al, 2012). Psychiatric disorders present a major burden for the individual and our society, placing them distant first in the global burden of disease statistics (Vigo, Thornicroft, & Atun, 2016).…”
Section: Introductionmentioning
confidence: 87%